Socio-Economic Impact of COVID-19 Pandemic on Small and Medium-scale Enterprises (SMEs) in India - Swaraj S Bharti (Annals of Management and Organization Research, 2021)
Purpose: Small and Medium-scale Enterprises (SMEs) face problems with a lack of funds and liquidity for remuneration to their employees, usage of technology, etc. Hence, the research study aims to identify the social and economic impact of the COVID-19 Pandemic on Small and Medium-scale Enterprises across the Nation. Research methodology: The data extraction procedure uses exploratory study with systematic review technique from the different directories of journals. A thorough qualitative and quantitative analysis based on peer-reviewed journals worldwide is conducted to recognize, ascribe, and explore the upcoming trends and to establish suggestions and recommendations for future research in this particular domain. Results: The study identified the significant social impact connected to the provision of limited capability regarding medical literacy and awareness and various social stigma, an obstacle in attaining the purpose of timely disease treatments in Small and Medium-scale Enterprises. The study further explored that gender biases and residential discrimination led to unfair treatment regarding healthcare facilities. Limitations: The study considers the COVID-19 Pandemic, whereas, in the future, there may be a possibility of other kinds of artificial or natural disasters. Novelty: The research mainly deals with the national effect of social factors during the crisis in addition to the economic impact on Small and Medium-scale Enterprises (SME).